FREQUENCY, INDICATIONS AND COMPLICATIONS OF PULMONARY ARTERY CATHETER INSERTION IN ADULT OPEN-HEART SURGERY PATIENTS OF A TERTIARY CARE HOSPITAL - Ahmed, Syed Shabbir; Akhtar, Mohammad Irfan; Kamal, Rehana (Journal of Ayub Medical College Abbottabad, 2016)
Background: Patients presenting for cardiac surgery have unstable cardiovascular disease and haemodynamics with multiple coexisting diseases. Optimal monitoring in the perioperative period is very important for best perioperative outcome. The introduction of the flow-directed pulmonary artery catheter (PAC) into clinical practice is one of the most important and popular advances in the field of cardiac anaesthesia. The objective of the study was to determine the frequency, indications and complications of pulmonary artery catheter insertion in adult open-heart surgery patients. Methods: A Prospective observational study was conducted at cardiac operating rooms and Cardiac Intensive care unit (CICU) of Aga Khan University Hospital for a period of six months from Nov 2015 to April 2016.Two hundred and seven patients were included in this study. PAC was inserted through right/left internal jugular vein or subclavian vein. Complications noted were arrhythmias (atrial and ventricular), right bundle branch block, coiling and knotting, pulmonary artery rupture, and infection up to 72 hours of PAC insertion. Frequency and percentage were computed for gender, comorbids (Hypertension, Diabetes, Chronic kidney disease, Chronic Obstructive Pulmonary Disease) and PAC frequency of insertion, indications and complications were noted. Results: The frequency of PAC insertion was 47.83%. Major indications for PAC insertion were poor left ventricular function, acute coronary syndrome, cardiogenic shock, significant left main disease and valvular heart disease patients. Minor complications were found in 23.22% cases, which included arrhythmia in 19.2% cases and coiling in 4.02%. Conclusion: Pulmonary artery catheter insertion is a safe technique with useful clinical application in the management of high-risk cardiac surgical patients. The PAC insertion rationale must be standardized to confirm the judicious use. Keywords: Pulmonary artery catheter (PAC) insertion; Adult cardiac surgery; Complications